AN ANALYSIS OF FIGURATIVE LANGUAGES USED IN COELHOS’S NOVEL ENTITLED “ALCHEMIST” - Trisna Dinillah Harya (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
The title of this study is, “An Analysis of Figurative Languages Used in Paulo Coelho’s novel Entitled “The Alchemist”. The objectives of the study are to describe the types of the figurative language found in the book and to identify the contextual meaning of the figurative language. The method used in collecting the data related to the subject of this research is documentation method because the researcher collected the data from novel. This study was conducted by collecting any relevant data and information about the topic or problem of the study from novels and internet that are available for the analysis. The data collection used the following steps: reading the novel, and then selecting the data that used the types of figurative language. While the steps to analyze the data are identifying the types of figurative language according to Leech, identifying the contextual meaning of the figurative language, and the last is interpreting the data.The result shows that there are 70 sentences that have figurative language. From all the sentences, there are 30 items or 42.9% of simile, 27 items or 38.6% of personification, 12 items or 17.1% of metaphor, and 1 item or 1.4% of hyperbole. It can be indicated that the dominant type of figurative language in the novel is simile. The author uses simile to explain circumstances, to describe the characters, to express emotion of the characters, and to make his writing more vivid and entertaining. It can be concluded that figurative language has important roles in this novel. That‘s why the author used so many sentences that have figurative language in this novel. Using figurative language makes the novel more interesting to read, and helps the readers to imagine the story, the character based on the illustration that the author has already given in the story.